Alcohol and substance use and associated risk factors in nursing undergraduates at a South African university - Kovane, Gaotswake P.; Mayers, Pat M. (Health SA = SA Gesondheid, 2025)
Background: The use of substances by university nursing students is a significant public health challenge and may impact their professional conduct and compromise the quality of patient care. Aim: The study aimed to investigate alcohol and substance use by undergraduate nursing students, and the associated risk factors, at a university in the Western Cape province, South Africa. Setting: The study was conducted at a university in the Western Cape province, South Africa. Methods: A quantitative, descriptive survey design was used. A convenience sample of second-, third- and fourth-year nursing students completed a self-report online questionnaire. Descriptive statistics, Chi-square tests and multivariate linear regression were used to analyse the data. Results: A total of 212 questionnaires were completed. Most respondents (81%; n = 171) were female. The substances most used were tobacco (24.1%), alcohol (64.6%) and cannabis (marijuana) (23.7%). Few students had used ‘hard’ recreational drugs. Female students were more likely to have used alcohol and drugs over the 12 months preceding the study. Conclusion: To limit alcohol and drug use of nursing students, nursing education institutions need to increase efforts to raise awareness, include relevant curriculum content and provide appropriate support. Contribution: This study highlights the substance use risks and behaviours of undergraduate nursing students. Nursing students, as future health professionals, need to be empowered to make informed choices about the use of alcohol and other substances and need to be supported by university policies, appropriate education and counselling services.